Est-ce que le chocolat noir a un effet ergogène sur le niveau de force? - Scholler, V.; Marcel-Millet, P.; Groslambert, A. (Movement & Sport Sciences - Science & Motricité, 2021)
The aim of this research is to assess the acute effect of consuming a dark chocolate with lemon (DCL) bar on the emotional state, the vegetative nervous system, and strength performance. This protocol was carried out by eleven male trained cyclists and trail runners (age: 27 ± 12 years old), who tested, in random order, either DCL bar containing flavonoids or a white chocolate bar (placebo) before a simulated competition of knee extension force. Their precompetitive state anxiety (SA), blood pressure, heart rate variability (HRV), and electroencephalography (EEG) responses were measured before and after eating the bars. The maximal voluntary force (MVC) of the knee extensor and the time to exhaustion (TTE) at 20% of MVC were recorded 2 h after eating the bars. Compared to placebo, DCL decreases significantly (p < 0.05) the SA and the systolic blood pressure. An increase of a and a decrease of ß waves with a moderate effect size (d = 0.7) were found in the prefrontal cortex, whereas no significant change was observed for HRV and MVC. However, an increase (+22%) of TTE with a moderate effect size (d = 0.5) was found. These findings suggest the potential role of flavonoids to decrease precompetitive anxiety as a complementary routine to improve strength performance.